Reply to ““Taxonomic certification versus the scientific method”: a rebuttal of Rogers (2012)” by Stribling et al., 2012 - Rogers, D. Christopher (Zootaxa, 2012)
I am grateful to Stribling et al., (2012) for pointing out two errors I made in my original opinion piece (Rogers, 2012), namely citing  Stribling et al., 2003 as Stribling et al., 2002, and stating that that same reference used the term “bench taxonomist” when in reality it was “production taxonomist”.